Economic assessment based on scenario analysis for the production of a new functional pasta. (November 2018) - Micale, R.; Giallanza, A.; Enea, M.; La Scalia, G.
Abstract: Nowadays functional foods are becoming more popular due to their capacity to prevent and/or reduce the risk of certain diseases. Functional foods improve health and give physiological benefits providing nutrients beyond the simple nutritional value. The market for functional foods is growing rapidly and the consumers are willing to pay a premium price for these products. In this context, the production of pasta comprising Opuntia may represent an opportunity to combine the widespread consumption of pasta in the traditional Mediterranean Diet and the beneficial characteristics of the Opuntia, including anti-inflammatory, antioxidant, hypoglycemic, antimicrobial and neuroprotective properties. The aim of this paper is to evaluate the economic feasibility of the production of dried pasta functionalized with an extract of cladodes from Opuntia Ficus Indica in an existing medium-size pasta factory. For this purpose, an economic evaluation based on scenarios analysis was conducted. In particular, in each scenario different percentages of Opuntia solution were considered and two different economic aspects were varied: the price of the functionalized pasta and the cost of the Opuntia solution that satisfies a fixed price for the final product. The economic evaluation was carried out on the basis of the Net Present Value and of the Investment Payback Time. Highlights: The production of pasta comprising Opuntia may represent an economic opportunity. The purpose of this paper is to asses the feasibility of different economic scenarios. Scenarios have been obtained by varying the main economic parameters involved in the production process. The economic evaluation was carried out considering the NPV and the Payback Time. Results show a framework to identify economic outcomes for the different scenarios.